2007
DOI: 10.1380/ejssnt.2007.33
|View full text |Cite
|
Sign up to set email alerts
|

Surface Energy Band and Electron Affinity of Highly Phosphorous-doped Epitaxial CVD Diamond

Abstract: The surface energy band diagrams and the electron affinity of hydrogen-terminated and oxygen-terminated highly phosphorous-doped single crystal diamond (111) surfaces have been studied by ultraviolet photoelectron spectroscopy, secondary electron spectroscopy, X-ray photoelectron spectroscopy and photoemission electron microspectroscopy. A hydrogen-terminated boron-doped diamond (001) surface was used as a reference of surface energy band diagram. The electron affinity of the H-terminated heavily P-doped diamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
0
13
1
Order By: Relevance
“…Taking our photoemission results for NEA into account, the contribution of the n + -layer with NEA to electron emission is not expected. 4,[6][7][8][9][10] In addition, the larger the carrier diffusion length, the larger the contribution of the electron emission with NEA. 4,10,16) It is reasonable that the diffusion lengths of free electrons and/or free excitons in the i-layer are larger than those in the p-layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking our photoemission results for NEA into account, the contribution of the n + -layer with NEA to electron emission is not expected. 4,[6][7][8][9][10] In addition, the larger the carrier diffusion length, the larger the contribution of the electron emission with NEA. 4,10,16) It is reasonable that the diffusion lengths of free electrons and/or free excitons in the i-layer are larger than those in the p-layer.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we previously revealed that an n-type surface with NEA induced by hydrogen termination does not show electron emission from the bulk, where a large upward band bending might exist. [7][8][9][10] In this study, we designed structures of p-i-n diode emitters for investigating emission sites. We changed the periphery length of p-i-n mesa diodes while maintaining the top area.…”
Section: Introductionmentioning
confidence: 99%
“…First, we pay attention to the relationship of the energy positions of field emission and photoemission peaks with those of work function and electron affinity of the P-doped (111) surface. As already mentioned, and of highly Pdoped diamond (111) have been studied very recently 13) and it showed that and of a H-terminated heavily P-doped diamond are about 3.8 and 0.2 eV, respectively. If we place the photoemission peak about 1 eV above CBM at the surface, the field emission peak comes right on the sample surface E F .…”
mentioning
confidence: 87%
“…[9][10][11] In the F-N analyses, the work function () and the electron affinity () of the surface were assumed to be identical to those of lightly P-doped 12) or intrinsic diamond (111) surfaces. and of highly P-doped diamond (111) have been studied very recently, 13) which showed that and of a H-terminated heavily P-doped diamond are $3:8 and $0:2 eV, respectively and that and of an O-terminated highly P-doped diamond are $3:9 and $0 eV, respectively. These values are quite different from those of lightly P-doped or intrinsic diamond (111).…”
mentioning
confidence: 99%
See 1 more Smart Citation